De 70 a 700 a 70.000: Lecciones del estudio de Jamaica - María Caridad Araujo; Marta Rubio-Codina; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2021)
– This document compares three versions of the same home visiting model, the well-known Jamaica model, which was gradually scaled-up from an efficacy trial (proof of concept) in Jamaica, to a pilot in Colombia, to an at-scale program in Peru. It first describes the design, implementation and impacts of these three programs. Then, it analyzes the threats to scalability in each of these experiences and discusses how they could have affected program outcomes, with a focus on three of the elements of the economic model of scaling in Al-Ubaydli, et al. (Forthcoming): appropriate statistical inference, properties of the population, and properties of the situation. The document reflects on the lessons learned to mitigate the threats to scalability and on how research and evaluation can be better aligned to facilitate and support the scaling-up process of early child development interventions. It points out those attributes that interventions must maintain to ensure effectiveness at scale. Similarly, political support is also identified as indispensable.
Keywords: I38; J24; O15; 330; home visiting; quality; child development; monitoring; scalability